Economic Corruption and its Impact on Achieving the Sustainable Development Goals (SDGs) in Libya (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This paper investigates the relationship between economic corruption and the achievement of Sustainable Development Goals (SDGs) in Libya. Utilizing time-series data from 1990 to 2019 and employing an Autoregressive Distributed Lag (ARDL) model, the paper assesses the impact of economic corruption, measured by the International Country Risk Guide (ICRG) index, on the Sustainable Development Index (SDI). The findings reveal a significant negative correlation between economic corruption and sustainable development. The paper further examines the roles of economic growth, human capital, inflation, and unemployment as key determinants influencing sustainable development outcomes. The results emphasize the need for comprehensive strategies to combat corruption, promote good governance, and foster inclusive economic development to accelerate progress toward the SDGs in Libya.